Sistem Klasifikasi Kelor dalam Etnobotani Masyarakat Wolio - Sofyani, Wa Ode Winesty (Fakultas Ilmu Sosial dan Ilmu Politik UIN Walisongo Semarang, 2019)
This article studies about ethnobotany kelor (Moringa oleifera) of Wolio people in Baubau, Southeast Sulawesi Province. The aim of this research is to know how the classification systems of kelor plants in Wolio people and why the kelor plants to be classified. Data collection of this research is using ethnography method, in-depth interview and participatory observation to know the view of Wolio people concern with kelor. The result of this research shows that kelor classification system of Wolio people consists of females and males. According to Wolio people, the existence of kelor classification due to a difference of colour, type, size, and taste. The use of kelor gender as kelor classification system reflects the life of Wolio people.Â Â